Mental well-being of children and adolescents during COVID-19: evidence from the Italian context and possible future developments - Francesco Orazi; Federico Sofritti; Davide Lucantoni (Frontiers in Sociology, 2024)
The article aims to discuss the increased emergence of mental health problems among children and adolescents, as an outcome of the COVID-19 pandemic.The results of a research study conducted among various professionals, such as psychiatrists and psychologists specialized in childhood and adolescence, are presented. The study, which uses both qualitative and quantitative methods, investigates the main consequences of the physical social distancing measures undertaken by the Italian government during the pandemic. The results are in line with the main evidence highlighted by international research and underline the particularly negative effects of the pandemic emergency on the mental health of minors. It reports how the limitation of intersubjective relationships and the forced digitalization of relationships has triggered or caused the emergence of multiple and varied disorders of the psyche, also linked to the area of reference (e.g., metropolitan, urban o remote areas), the socio-economic and cultural fragility of families, as well as the presence of previous mental issues within them. Finally, the research emphasizes how the understanding and management of the psychic health of these population groups, also from a health organization point of view, will be crucial to address the medium and long-term effects of such emerging issues among younger cohorts.